Analysis of Leadership Style and Working Hours in Improving Employee Performance at PT. Citra Kendedes Cake and Bakery Malang City - Emiliana; Cakti Indra Gunawan; Imam Hidayat (International Research & Development for Human Beings (IRDH), 2025)
Human Resources management is the key to organizational success, where leadership style and working hour arrangements significantly affect employee performance. PT Citra Kendedes Cake and Bakery in Malang face challenges related to employee performance due to suboptimal leadership and unintegrated working hour management. This study aims to analyze the role of leadership style, the contribution of working hours, and the interaction between the two in improving employee performance. A descriptive qualitative method was used with data collection techniques through in-depth interviews and participatory observation of HRD and supervisors. The results show that a situational and adaptive leadership style that combines a democratic approach, flexibility, and SOP support successfully creates a collaborative work environment. A standardized working hours policy (8 hours/day) with flexibility for supervisors and transparent overtime compensation improved employee productivity and welfare. However, challenges such as policy communication inconsistencies and procedural ambiguities need to be addressed through strengthening documentation systems and leadership training. The synergy between adaptive leadership and humane working hour arrangements proved effective in improving performance, although it requires refinement of the operational structure to minimize the risk of employee fatigue.